Acute Spinal Cord Contusion in a Patient with Multiple Upper Cervical Fractures, Parkinson’s Disease, and Torticollis: Surgical Management - Sarah Merrill; Maziyar A. Kalani; Naresh P. Patel; Mark K. Lyons; Matthew T. Neal (Case Reports in Orthopedics)
Case Report. Spine surgery in patients with Parkinson’s disease (PD) involves increased risk. We describe a case of cervical myelopathy in a patient with PD, multiple fractures involving the atlas and axis vertebrae, and spasmodic torticollis. The patient was successfully treated with an upper cervical decompression and occipital-cervical (OC) fusion surgery. Strategies for torticollis reduction and successful surgical outcome are discussed. Risks and benefits must be carefully weighed when considering occipital cervical fusion in PD patients. Conclusion. Intraoperative manual reduction of laterocollis is possible after general endotracheal anesthesia, and continuous neuromonitoring is established. Use of optimizing strategies such as perioperative botulinum injections and intraoperative O-arm navigation should be considered.